The Main Therapeutic Applications of Cannabidiol (CBD) and Its Potential Effects on Aging with Respect to Alzheimer's Disease - Trojan, Václav; Landa, Leoš; Šulcová, Alexandra; Slíva, Jiří; Hřib, Radovan (Biomolecules, 2023)
The use of cannabinoids (substances contained specifically in hemp plants) for therapeutic purposes has received increased attention in recent years. Presently, attention is paid to two main cannabinoids: delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). With respect to the psychotropic effects and dependence potential of THC (though it is very mild), its use is associated with certain restrictions, and thus the therapeutic properties of CBD are frequently emphasized because there are no limitations associated with the risk of dependence. Therefore, this review covers the main pharmacodynamic and pharmacokinetic features of CBD (including characteristics of endocannabinoidome) with respect to its possible beneficial effects on selected diseases in clinical practice. A substantial part of the text deals with the main effects of CBD on aging, including Alzheimer's disease and related underlying mechanisms.
Keywords: Cannabinoids; Cannabidiol; kanabidiol; tetrahydrokanabinol; Alzheimer’s disease; cannabinoids; Alzheimerova nemoc; kanabinoidy; Alzheimer Disease; cannabidiol; lidé; aging; Humans; Dronabinol